2018
DOI: 10.3390/nu10081007
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Health Aspects in Polish Consumer Choices of Dairy Products

Abstract: In general, dairy products are well regarded for their nutritional value. Consumer perception of dairy products is influenced by many interrelated factors but healthiness remains one of the key attributes and values for consumers. Furthermore, contemporary consumers increasingly seek out dairy products with additional health benefits and, therefore, it is essential to explore which attributes are important drivers of food choices and how producers can better respond to shifting consumer values and needs in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
1
18
0
1
Order By: Relevance
“…Fermentation may enhance the benefits of a wide variety of foods, dairy products, herbs, and beverages, acting upon the absorption and activity of their secondary metabolites and chemical elements [86]. However, it is not always possible to clearly distinguish the potential contribution of the microbial content from that of the food matrix.…”
Section: Fermented Foods Probiotics Body and Mindmentioning
confidence: 99%
“…Fermentation may enhance the benefits of a wide variety of foods, dairy products, herbs, and beverages, acting upon the absorption and activity of their secondary metabolites and chemical elements [86]. However, it is not always possible to clearly distinguish the potential contribution of the microbial content from that of the food matrix.…”
Section: Fermented Foods Probiotics Body and Mindmentioning
confidence: 99%
“…The demand for high quality food has constantly increased during recent decades, as has the interest in the food quality issue both in response to market pressure (such as requests from increasingly demanding and knowledgeable consumers) and also as a reaction to other factors, for example health and environmental concerns [1]. The consumer of the 21st Century is a highly demanding one, exhibiting greater concern about quality and health benefits with respect to products he/she buys [2]. Food quality is a central issue in today's food economics [3], and the last few decades testify that consumers' concerns for healthier lifestyles and environment care are driving forces for reshaping food buying intentions and their perspectives on food quality.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have investigated the effect of bovine dietary supplementation of individual AAs on milk gross composition [6,7] and protein synthesis [8], little information exists on the potential effect of standard bovine feeding systems on the overall AA composition of milk. Recently, consumer interest has increasingly been focused on dairy products derived from what is perceived as a healthier [9], natural, or more sustainable, origin [10]. While previous research has demonstrated the effect of diet on the fat fraction of milk, the micronutrient composition of various protein ingredients is an important consideration in the manufacture of dairy products which aim to meet this demand.…”
Section: Introductionmentioning
confidence: 99%